2023
DOI: 10.1039/d2cc06011f
|View full text |Cite
|
Sign up to set email alerts
|

Biological anolyte regeneration system for redox flow batteries

Abstract: Redox flow battery (RFB) electrolyte degradation is a common failure mechanism in RFBs. We report an RFB using genetically engineered, phenazine-producing Escherichia coli to serve as an anolyte regeneration system...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The general procedural protocol for immobilizing bacteria on the anode surfaces follows previously established experimental steps by our research group, reported elsewhere. , To characterize the anode half-cells, AvCarb carbon paper (AvCarb MGL 190, Fuel Cell Store) was cut to obtain working electrodes with an area of 1 cm 2 . For MFC setup and operation, carbon cloth electrodes (Carbon Cloth CC4 Plain, Fuel Cell Store) with an area of 6.5 cm 2 were used as the anode material.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general procedural protocol for immobilizing bacteria on the anode surfaces follows previously established experimental steps by our research group, reported elsewhere. , To characterize the anode half-cells, AvCarb carbon paper (AvCarb MGL 190, Fuel Cell Store) was cut to obtain working electrodes with an area of 1 cm 2 . For MFC setup and operation, carbon cloth electrodes (Carbon Cloth CC4 Plain, Fuel Cell Store) with an area of 6.5 cm 2 were used as the anode material.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These SWV results show distinct redox potential signatures at −0.21 and −0.39 V versus SCE, which correspond to PYO and PCA, respectively, and agree with the redox potential values for these phenazines reported by previous research studies. 49,66 For these experiments, we took voltammetric measurements every hour for the initial 1−6 h, followed by every 2 h, followed by 13 h, and finally followed by 3 h of the 30-h bacterial growth period on the conductive carbon paper electrodes. As phenazine production by the genetically engineered E. coli cells increases, the peak currents for PCA and PYO in the CV and SWV data increase accordingly.…”
Section: Genetically Engineering Phenazine Biosynthesismentioning
confidence: 99%
“…The possible chemical decomposition mechanisms of organic redox‐active materials include dimerization, tautomerization, hydrolysis, disproportionation, and nucleophilic addition/substitution 27,37,68,97,98 . In addition, biological electrolyte regeneration systems, such as the use of Escherichia coli to regenerate the degraded/decomposed redox‐active phenazines in the anolyte, may provide a possibility to further enhance the stability of RFBs 99 . So far, several recent reviews have well summarized the possible capacity degradation mechanisms of AORFBs 68–70 .…”
Section: Capacity Degradation Mechanism Studiesmentioning
confidence: 99%
“…27,37,68,97,98 In addition, biological electrolyte regeneration systems, such as the use of Escherichia coli to regenerate the degraded/decomposed redox-active phenazines in the anolyte, may provide a possibility to further enhance the stability of RFBs. 99 So far, several recent reviews have well summarized the possible capacity degradation mechanisms of AORFBs. [68][69][70] Interested readers can access these studies and reviews for more detailed information.…”
Section: Capacity Degradation Mechanism Studiesmentioning
confidence: 99%
“…A wide body of literature exists on many different types of mediators and mediator modifications to tune their redox potential in accordance with the wide potential range of redox cofactors. Common redox mediators can include metal complexes and polymers (e. g. osmium), [45] metallocene molecules (e. g. ferrocene or cobaltocene), [20,46] quinones,, [47][48] phenazines, [49][50][51][52][53] and viologens [19,54] (Figure 6).…”
Section: Charge Transfer Mechanisms: Direct and Mediated Electron Tra...mentioning
confidence: 99%